LIQUID SMOKE SUBMERSIVE EFFECTIVENESS OF ACRYLIC PLATE TO THE GROWTH OF CANDIDA ALBICANS - Mochamad Haldi Tri Hutama; Windriyatna Windriyatna; Dwi Ngestiningsih; RR Mahayu Dewi Ariani; Tyas Prihatiningsih (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: Acrylic denture was an alternative to replace a lost tooth, and surrounding tissues have the part of the acrylic plate, which was frequently a place of Candida albicans proliferation. The liquid smoke has a chemical compound of phenol which produced antimicrobial and could hamper or destroy Candida albicans.Objectives: To identify the acrylic plate's effectiveness, soaking into liquid smoke to the growth of Candida albicans.Methods: This research was categorized into experimental research which exerted post-test control group research design. The total sample in this research was 25 samples, four treatment groups, and one control group. This treatment covered acrylic plate soaking into liquid smoke in specific concentration level 1%, 2%, 4%, and 6% to obstruct the growth of Candida albicans. Moreover, the statistic test was conducted through Kruskal-Wallis and continued to Post-Hoc test through Mann-Whitney theory.Findings: This research showed a significant difference between the amount of Candida albicans on the control group and liquid smoke group in concentrations 1%, 2%, 4%, and p-valuable = 0,005). Further, based on the Post-Hoc test result of Mann-Whitney, it referred significant difference between concentrations 1%, 2%, 4%, and 6% within sterile aquades (p-value = 0,008).Conclusions: The liquid smoke shared effective concentration which functioned to hamper Candida albicans on the acrylic plate. The concentration level of 6% was the most effective concentration to interfere Candida albicans on the acrylic plate. Furthermore, it was not found any significant difference between resistibility of liquid smoke to Candida albicans on an acrylic plate with concentration level of 1%-6% which could be the most effective way to obstruct Candida albicans on acrylic plate.Keywords : Acrylic plate, Liquid smoke, Candida albicans